Analisis Tingkat Literasi Masyarakat Kabupaten Kuningan Mengenai Zakat dengan Menggunakan Indeks Literasi Zakat (ILZ) - Dewi Tri Utami; Ikhwan Hamdani; Santi Lisnawati (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to measure the Zakat Literacy Index (ILZ) of the Kuningan Regency community using the Simple Weighted Index method, which focuses on measuring a person's level of understanding and literacy on the object of zakat. Literacy and understanding of zakat is an external aspect that can determine a person in making decisions in paying zakat. The results of this study indicate that the Zakat Literacy Index (ILZ) of the Kuningan Regency community gets a value of 83.12 which is counted in the high literacy category. The highest indicator in this study is the variable knowledge of zakat in general with a score of 94.03. And the lowest indicator in this measurement lies in the variable knowledge of digital payment zakat with a score of 51.35. Keywords: Literacy, Measurement, Zakat Literacy Index